Interspecific hybridisation in tuart (Eucalyptus gomphocephala, Myrtaceae): A conservation management issue? - Wheeler, R.; Nevill, Paul; Renton, M.; Krauss, S. (2013)
The anthropogenic movement of Eucalyptus species beyond their natural distributions is increasing the opportunity for interspecific hybridisation. The conservation implications arising from hybridisation between indigenous and introduced eucalypt species in modified urban landscapes is an increasingly important management issue that requires an assessment of risk. It has been claimed that much of the tuart (Eucalyptus gomphocephala DC., Myrtaceae) seed in Kings Park, a large urban bushland remnant in Perth, Western Australia, is of hybrid origin with introduced eastern Australian eucalypts, and especially with E. cladocalyx. Using molecular markers, we tested this claim and determined whether hybridisation in tuart is a conservation management issue in Kings Park, as well as the adjacent Bold Park. Eight microsatellite markers were used to genotype 220 open-pollinated tuart seedlings from 19 families. Allele frequency estimates for tuart were generated by genotyping 42 mature tuart trees. Forty-four trees of four alternative species thought to be capable of hybridising with tuart in these parks, including two non-indigenous species, E. cladocalyx and E. camaldulensis, and two indigenous species, E. decipiens and E. rudis, were also genotyped. Pairwise FST between tuart and each alternative species for these markers ranged from 0.105 to 0.204. A hybrid-index analysis of seedling genotypes showed no significant evidence for hybridisation, and no alternative species private alleles (n = 35) were found in any tuart offspring genotypes. A likelihood analysis showed that the maximum likelihood of observing no private alleles of the alternative species in the progeny occurred at a hybridisation frequency of zero for all four alternative species. We conclude that hybridisation between tuart and non-indigenous species is not currently a conservation management issue in Kings Park and Bold Park. Rather, the invasion of pure non-indigenous species, and in particular E. cladocalyx, as weeds into bushland is of greater management concern.